DEVELOPMENT AND VALIDATION OF LIQUID CHROMATOGRAPHY AND SPECTROSCOPIC METHODS FOR THE ANALYSIS OF DOXOFYLLINE IN PHARMACEUTICAL DOSAGE FORMS - Ethiraj Thiruvengadam; Revathi Ramadoss; Ganesan Vellaichamy (Universitas Gadjah Mada, 2013)
A high performance liquid chromatography (HPLC) and ultraviolet spectroscopic (UV) methods were developed and validated for the quantitative estimation of doxofylline (DF) in pharmaceutical dosage forms. HPLC was carried out using reversephase technique on RP-8 column with a mobile phase composed of 0.05M phosphate buffer pH 6 and acetonitrile (60:40, v/v). The mobile phase was pumped at a flow rate of 1mL/min, and detection was made at 230nm with PDA detector. UV method was performed with λ max at 270nm with apparent molar absorptive of 0.878x103 L mol-1 cm-1. Both the methods showed good linearity, recovery and precision. No spectral or chromatographic interferences from the tablet excipients were found in UV and HPLC methods. The various parameters such as linearity, precision, accuracy, specificity, and robustness, limit of detection and limit of quantization were studied according to ICH guidelines. Statistical analysis was done by student's t-test and F-test, which showed no significant difference between the results of both methods. So the proposed methods could be applicable for routine analysis of DF and monitoring of the quality of marketed drugs.